Konferencja nt. „Szkolnictwo kościelne w Rzeczypospolitej od XVI do XIX w.” - Nowicki, Michał (Biuletyn Historii Wychowania, 2010)
Konferencja nt. „Szkolnictwo kościelne w Rzeczypospolitej od XVI do XIX w.”